Long-fiber non-woven fabric, airbag packaging material comprising same, and method for producing long-fiber non-woven fabric
By using a long fiber non-woven fabric made of fibers with a thermoplastic resin as the main component, and using a composite fiber structure of a high melting point polymer and a low melting point polymer, the problems of deterioration of storage properties and damage and cracks caused by the increase of tensile strength of the long fiber non-woven fabric in a specific direction in the prior art are solved, and the softness and mechanical strength of the airbag storage member are taken into consideration.
Patent Information
- Application Number
- CN202380053120.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-29
- Filing Date
- 2023-05-15
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, the tensile strength of the long fiber nonwoven fabric increases in a specific direction, resulting in a deterioration of the storage property in the storage member, and it is prone to breakage or cracking when in contact with the storage member.
A long fiber nonwoven fabric made of fibers mainly composed of thermoplastic resin, the average single fiber diameter of the fiber is 10.0 μm or more and 20.0 μm or less, and the cross-sectional void ratio is 30% or more and 80% or less. The mechanical strength and flexibility of the fiber are enhanced by a composite fiber structure of a high melting point polymer and a low melting point polymer.
The softness and mechanical strength of the airbag storage member are achieved, the risk of damage and cracking during the storage process is avoided, and the advantages of the storage operation are improved.
Smart Images

Figure BDA0005236822410000241
Abstract
Description
Technical Field
[0001] The invention relates to a long-fiber nonwoven fabric, a safety airbag packaging material containing the long-fiber nonwoven fabric, and a method for producing the long-fiber nonwoven fabric. Background Art
[0002] The airbag packaging material has the following functions: to store the folded airbag and prevent the stored airbag from accidentally deploying or deviating from the stored position, and to protect it from contacting with the components storing the airbag such as the hub of the steering wheel (hereinafter sometimes referred to as the storage component) when installed and fixed to the vehicle. Therefore, the airbag packaging material is required to have flexibility to follow the shape of the device of the storage component and mechanical strength not to be damaged or cracked when in contact with the storage component.
[0003] The airbag packaging material may use nonwoven fabrics, and some proposals have been proposed so far as a technology for achieving both the softness and mechanical strength of nonwoven fabrics. For example, Patent Document 1 proposes an airbag cover characterized by being formed of a fabric having a ratio of longitudinal to transverse tensile strength within a specific range, a tensile strength of one of the fabrics being greater than a certain value, and a weight per unit area within a specific range.
[0004] In addition, Patent Document 2 proposes a packaging material for storing a curtain-like airbag, which is a packaging material for storing a curtain-like airbag arranged on the side of a vehicle body and expands into a curtain shape when a high load is applied and unfolds in a manner covering the side of the vehicle body. The packaging material is characterized in that the packaging material is obtained from a thermoplastic synthetic fiber non-woven fabric, the unit area weight and average apparent density of the non-woven fabric are within a specific range, the longitudinal tensile strength, elongation at break, tear strength and rupture strength are above a certain level, and the stiffness is within a certain range.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2005-1622
[0008] Patent Document 2: Japanese Patent Application Publication No. 2003-306118 Summary of the invention
[0009] Problems to be solved by the invention
[0010] The technologies proposed in Patent Documents 1 and 2 are nonwoven fabrics with high tensile strength in a specific direction, so they have certain mechanical properties and can achieve compact storage to a certain extent. However, if the tensile strength in a specific direction increases and the aspect ratio of strength increases, it will become difficult to follow the direction of strong strength, and the storage property in the storage component will deteriorate. In addition, in the direction of weak strength, there is a high possibility of damage and cracking when contacting the storage component.
[0011] Therefore, an object of the present invention is to provide a long-fiber nonwoven fabric having flexibility that allows it to follow the device form of an airbag storage member and excellent mechanical strength that does not cause damage or tearing when in contact with the airbag storage member.
[0012] Means for solving problems
[0013] In order to solve the above-mentioned problems, the present invention has the following configuration.
[0014] [1] A long fiber nonwoven fabric comprising fibers mainly composed of a thermoplastic resin, wherein the average single fiber diameter of the fibers is not less than 10.0 μm and not more than 20.0 μm, and the cross-sectional void ratio of the long fiber nonwoven fabric is not less than 30% and not more than 80%.
[0015] [2] The long fiber nonwoven fabric according to [1] above, wherein the fibers are composite fibers in which a low melting point polymer having a melting point lower than that of the high melting point polymer is disposed around a high melting point polymer.
[0016] [3] The long-fiber nonwoven fabric according to [1] or [2], wherein the weight per unit area of the long-fiber nonwoven fabric is 20 g / m 2 Above 100g / m 2 the following.
[0017] [4] A long-fiber nonwoven fabric as described in any one of [1] to [3] above, wherein the tear strength of the long-fiber nonwoven fabric in the longitudinal direction and the cross direction is 30 N to 120 N, and the tensile elongation in the longitudinal direction and the cross direction is 10% to 40%.
[0018] [5] An air bag packaging material comprising the long-fiber nonwoven fabric according to any one of [1] to [4] above.
[0019] [6] The method for producing a long-fiber nonwoven fabric according to any one of [1] to [4], wherein the following steps (a) to (c) are performed in sequence.
[0020] (a) A step of melt-extruding a thermoplastic resin from a spinneret and pulling and stretching the spun thermoplastic resin using an ejector to form fibers.
[0021] (b) A step of controlling the arrangement of the fibers using a fiber spreading sheet and depositing the fibers on a moving net conveyor to form a fiber web.
[0022] (c) The obtained fiber web is preheated and then subjected to a thermal bonding step.
[0023] It should be noted that in the above [4], the so-called "length direction of the long fiber non-woven fabric" refers to the sheet conveying direction when the long fiber non-woven fabric is manufactured (the winding direction of the non-woven fabric roll), and the so-called "cross direction of the long fiber non-woven fabric" refers to the direction perpendicular to the sheet conveying direction (the winding direction of the non-woven fabric roll) when the long fiber non-woven fabric is manufactured.
[0024] Effects of the Invention
[0025] The long fiber nonwoven fabric of the present invention maintains a moderate density and has advantages in the sewing operability of the airbag packaging material. In addition, since it is a nonwoven fabric with excellent mechanical strength, it will not be damaged or torn when the airbag is stored in the airbag component, and the storage operability is excellent. DETAILED DESCRIPTION
[0026] The long fiber nonwoven fabric of the present invention is obtained from fibers mainly composed of thermoplastic resin, the average single fiber diameter of the above-mentioned fibers is 10 μm to 20 μm, and the cross-sectional void ratio of the long fiber nonwoven fabric is 30% to 80%.
[0027] Hereinafter, the components will be described in detail. However, the present invention is not limited to the scope of the following description unless it exceeds the gist of the present invention. Various changes can be made within the scope of the gist of the present invention.
[0028] [Fibers containing thermoplastic resin as the main component]
[0029] First, the long fiber nonwoven fabric of the present invention is obtained from a fiber whose main component is a thermoplastic resin. Here, in the fiber of the present invention, the so-called "main component is a thermoplastic resin" means that the mass of the thermoplastic resin relative to the mass of the entire fiber is more than 50% by mass. As the thermoplastic resin, for example, polyester, polyamide, polyolefin, or a mixture or copolymer thereof can be cited. Among them, polyester is preferably used from the perspective of excellent durability such as mechanical strength, heat resistance, water resistance, and chemical resistance.
[0030] Polyester is a high molecular polymer with an acid component and a diol component as monomers. In the present invention, as the acid component, aromatic carboxylic acids such as phthalic acid (ortho-propene), isophthalic acid and terephthalic acid, aliphatic dicarboxylic acids such as adipic acid and decanedicarboxylic acid, and alicyclic dicarboxylic acids such as cyclohexanecarboxylic acid can be used. In addition, as the diol component, ethylene glycol, diethylene glycol and polyethylene glycol can be used.
[0031] Specific examples of the polyester include polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polyethylene naphthalate (PEN), polylactic acid (PLA), and polybutylene succinate (PBS). As the polyester used as the high melting point polymer described later, polyethylene terephthalate (PET) is most preferably used because it has a higher melting point, excellent heat resistance, and excellent rigidity.
[0032] Additives such as crystal nucleating agents, matting agents, pigments, mildewproofing agents, antibacterial agents, flame retardants, metal oxides, aliphatic bisamides and / or alkyl-substituted aliphatic monoamides, and hydrophilic agents may be added to these polyester raw materials within the range that does not impair the effects of the present invention. Among them, metal oxides such as titanium oxide have the following effects: by reducing the surface friction of the fiber and preventing the fusion of the fibers, the spinnability is improved. In addition, when the long-fiber non-woven fabric is fusion-formed by a hot roller, the fusion property of the long-fiber non-woven fabric is improved by increasing the thermal conductivity. In addition, aliphatic bisamides such as ethylenebisstearic acid amide and / or alkyl-substituted aliphatic monoamides have the effect of improving the demoulding property between the hot roller and the non-woven web and improving the conveying property.
[0033] The fiber used in the present invention is preferably a composite fiber in which a low melting point polymer having a melting point lower than that of the high melting point polymer is arranged around a high melting point polymer. By adopting such a composite fiber, the fibers are easily and firmly fused in the long fiber nonwoven fabric, and as a result, the fuzzing of the surface of the long fiber nonwoven fabric can be suppressed, and a smooth surface can be easily obtained. Furthermore, the fibers constituting the long fiber nonwoven fabric are firmly fused to each other, and the number of fusion points between the fibers in the long fiber nonwoven fabric can also be increased compared to a fiber obtained by mixing fibers having different melting points, so that the mechanical strength can also be improved.
[0034] The difference between the melting point of the high melting point polymer and the melting point of the low melting point polymer (hereinafter sometimes referred to as "melting point difference") is preferably 10°C to 140°C. In other words, it is preferably a low melting point polymer having a melting point in the range of 10°C to 140°C lower than the melting point of the high melting point polymer. By making the difference in melting point preferably 10°C or more, more preferably 20°C or more, and further preferably 30°C or more, the fusibility between the fibers can be improved. In addition, by making the difference in melting point preferably 140°C or less, more preferably 120°C or less, and further preferably 100°C or less, when the fibers are fused to each other, the low melting point polymer component can be suppressed from fusing to the hot roller, which can reduce the fuzzing on the surface of the long fiber nonwoven fabric, and further reduce the defects generated on the surface of the long fiber nonwoven fabric.
[0035] In the present invention, the melting point of the high melting point polymer in the composite fiber is preferably in the range of 160°C to 320°C. By setting the melting point of the high melting point polymer in the composite fiber to preferably 160°C or more, more preferably 170°C or more, and even more preferably 180°C or more, when used as an air bag packaging material, for example, a long fiber nonwoven fabric having excellent morphological stability and capable of maintaining its shape even when subjected to processing such as heat application can be obtained. In addition, by setting the melting point of the high melting point polymer in the composite fiber to 320°C or less, more preferably 300°C or less, and even more preferably 280°C or less, it is possible to suppress a situation in which the heat energy used for melting is greatly consumed during the production of the long fiber nonwoven fabric, thereby reducing productivity.
[0036] On the other hand, the melting point of the low melting point polymer in the composite fiber is preferably in the range of 150°C to 310°C while ensuring the above-mentioned difference in melting points. By setting the melting point of the low melting point polymer in the composite fiber to preferably 150°C or more, more preferably 160°C or more, and further preferably 170°C or more, when the long fiber nonwoven fabric is used as an airbag packaging material, it is possible to obtain a long fiber nonwoven fabric having excellent morphological stability and being able to maintain its shape even when subjected to processing such as applying heat. In addition, by setting the melting point of the low melting point polymer in the composite fiber to preferably 310°C or less, more preferably 290°C or less, and further preferably 270°C or less, it is possible to obtain excellent fusion properties when manufacturing the long fiber nonwoven fabric, and it is possible to easily obtain a long fiber nonwoven fabric having excellent mechanical strength.
[0037] It should be noted that in the present invention, the melting point of the thermoplastic resin is measured using a differential scanning calorimeter ("DSC-2" model manufactured by PerkinElmer Co., Ltd. or a differential scanning calorimeter having equivalent performance) at a temperature increase rate of 20°C / min and a measurement temperature range of 30°C to 350°C, and the temperature at which an extreme value appears in the obtained melting endothermic curve is taken as the melting point of the thermoplastic resin. In addition, for a resin whose melting endothermic curve does not show an extreme value in the differential scanning calorimeter, the resin is heated on a hot plate and observed under a microscope, and the temperature at which the resin melts is taken as the melting point.
[0038] When the thermoplastic resin is polyester, as a combination of a high melting point polymer and a low melting point polymer (hereinafter, sometimes described in the order of high melting point polymer / low melting point polymer), for example, a combination of PET / PBT, PET / PTT, PET / polylactic acid, and PET / copolymer PET can be cited. Among these, a combination of PET / copolymer PET is preferably used from the aspect of excellent spinnability. In addition, as a copolymer component of the copolymer PET, isophthalic acid copolymer PET is preferably used from the aspect of excellent spinnability.
[0039] Regarding the composite form of the composite fiber, for example, a concentric core-sheath type, an eccentric core-sheath type, and an island type can be cited, among which the concentric core-sheath type is preferred from the aspect of being able to weld the fibers uniformly and firmly. Further, as the cross-sectional shape of the composite fiber, a circular cross-section, a flat cross-section, a polygonal cross-section, a multi-lobed cross-section, and a hollow cross-section can be cited. Among them, as the cross-sectional shape of the composite fiber, a circular cross-section is preferably used.
[0040] In addition, the content ratio of the high melting point polymer to the low melting point polymer in the fiber mainly composed of thermoplastic resin is preferably in the range of 90:10 to 60:40 in terms of mass ratio, and the range of 85:15 to 70:30 is more preferred. By making the high melting point polymer 60% to 90% by mass, the durability of the long fiber nonwoven fabric can be excellent. On the other hand, by making the low melting point polymer 10% to 40% by mass, the fibers constituting the long fiber nonwoven fabric are firmly fused to each other, and a long fiber nonwoven fabric with excellent mechanical strength can be made.
[0041] The average single fiber diameter of the fiber used in the present invention is 10.0 μm or more and 20.0 μm or less. Regarding the range of the average single fiber diameter, the lower limit is 10.0 μm or more, preferably 10.5 μm or more, and more preferably 11.0 μm or more, thereby making it possible to produce a long fiber nonwoven fabric with excellent mechanical strength. On the other hand, regarding the range of the average single fiber diameter, the upper limit is 20.0 μm or less, preferably 19.0 μm or less, and more preferably 18.0 μm or less, thereby improving the uniformity of the long fiber nonwoven fabric and making a long fiber nonwoven fabric with a dense surface. For example, when the long fiber nonwoven fabric is subjected to post-processing such as flame retardant processing as an airbag packaging material, the uneven coating of the processing agent can be reduced.
[0042] In addition, in this invention, the average single fiber diameter (micrometer) of a long-fiber nonwoven fabric adopts the value calculated|required by the following method.
[0043] (i) Ten small pieces of samples were randomly collected from the long fiber nonwoven fabric.
[0044] (ii) Using a scanning electron microscope (hereinafter referred to as SEM, "VHX-D500" manufactured by KEYENCE CORPORATION or an SEM having equivalent performance), a photograph of the surface of the collected small sample is taken. The photograph can measure the thickness of the fiber in a range of 500 to 2,000 times.
[0045] (iii) From the photographs of each small sample, 10 fibers were randomly selected one by one, totaling 100 fibers, and their thickness was measured. Assuming that the cross section of the fiber was circular, the thickness was taken as the fiber diameter.
[0046] (iv) The value calculated by rounding off the arithmetic mean value to the second decimal place was defined as the average single fiber diameter.
[0047] [Long fiber nonwoven fabric]
[0048] The long-fiber nonwoven fabric of the present invention is obtained from the aforementioned fiber having a thermoplastic resin as a main component. Here, the "long-fiber nonwoven fabric" in the present invention refers to a nonwoven fabric such as a spunbonded nonwoven fabric and a meltblown nonwoven fabric produced by the production method described below, and does not include a nonwoven fabric (short-fiber nonwoven fabric) consisting only of fibers cut into a certain length (e.g., 100 mm).
[0049] The cross-sectional void ratio of the long-fiber nonwoven fabric of the present invention is 30% or more and 80% or less. The lower limit of the cross-sectional void ratio is 30% or more, preferably 33% or more, and more preferably 35% or more, thereby preventing the fiber surface from becoming a sheet-like form like a film, and making it possible to produce a long-fiber nonwoven fabric with moderate softness. On the other hand, the upper limit of the cross-sectional void ratio is 80% or less, preferably 75% or less, and more preferably 70% or less, thereby making it possible to produce a long-fiber nonwoven fabric with excellent mechanical strength by firmly fusing the fibers constituting the long-fiber nonwoven fabric to each other.
[0050] Here, the value of the cross-sectional void ratio (%) in the present invention is a value obtained as follows.
[0051] (i) Ten small pieces of samples whose cross sections can be observed are collected from the long-fiber nonwoven fabric.
[0052] (ii) Using a SEM (“VHX-D500” manufactured by KEYENCE CORPORATION or an SEM having equivalent performance), a photograph of the cross section of the collected small piece sample is taken at 1,200 times magnification.
[0053] (iii) The photograph of each small sample was cut into a size of 50 μm×50 μm.
[0054] (iv) Each of the cut photos is converted into a grayscale image (8-bit image) and a threshold is set so that pixel values of 0 to 127 are black and 128 to 255 are white, thereby performing binarization.
[0055] (v) Using image analysis software ("ImageJ" or software having an equivalent function), the ratio of the black area to the entire photograph (white area, black area) is taken as the cross-sectional porosity.
[0056] (vi) The cross-sectional void fraction (%) is calculated similarly for 10 small-piece samples, and the arithmetic mean (%) of the cross-sectional void fractions of the 10 small-piece samples is calculated.
[0057] (vii) The arithmetic mean value (%) of the cross-sectional void ratios of the ten small sample pieces obtained in (vi) was rounded off to the first decimal place, and the value was defined as the cross-sectional void ratio (%) of the long-fiber nonwoven fabric.
[0058] Examples of methods for adjusting the cross-sectional void ratio of the long-fiber nonwoven fabric to the above range include preheating before thermal bonding as described below, and adjusting the average single fiber diameter of fibers constituting the long-fiber nonwoven fabric.
[0059] The weight per unit area of the long fiber nonwoven fabric in the present invention is preferably 20 g / m 2Above 100g / m 2 The lower limit of the weight per unit area of the long-fiber nonwoven fabric is preferably 20 g / m 2 More preferably 30g / m 2 More preferably, 40 g / m 2 On the other hand, regarding the range of the weight per unit area of the long-fiber nonwoven fabric, the upper limit is preferably 100 g / m 2 Below, preferably 90g / m 2 Below, more preferably 80g / m 2 As a result, a long-fiber nonwoven fabric which is lightweight and has excellent handling properties is obtained.
[0060] In the present invention, the basis weight of the long-fiber nonwoven fabric is a value measured by the following procedure in accordance with "6.2 Mass per unit area" of JIS L 1913:2010 "General nonwoven fabric test methods".
[0061] (i) Take three test pieces of 25 cm x 25 cm for every 1 m of sample width.
[0062] (ii) Weigh the respective masses (g) under standard conditions.
[0063] (iii) The average value is calculated per 1m 2 Mass (g / m 2 ) to indicate.
[0064] The thickness of the long-fiber nonwoven fabric in the present invention is preferably 0.10 mm or more and 0.30 mm or less. When the thickness is within the above range, the long-fiber nonwoven fabric is excellent in sewing workability of the airbag wrapping material and storage property in the airbag component.
[0065] In addition, in this invention, the thickness of a long-fiber nonwoven fabric adopts the value measured by the following procedure.
[0066] (i) The thickness of the long-fiber nonwoven fabric is measured at intervals of 10 cm in the cross direction using a thickness meter ("TECLOCK" (registered trademark) SM-114 manufactured by TECLOCK Co., Ltd. or a thickness meter having equivalent performance).
[0067] (ii) The third decimal place after the above arithmetic mean is rounded off to obtain the thickness (mm) of the long-fiber nonwoven fabric.
[0068] The apparent density of the long fiber nonwoven fabric of the present invention is preferably 0.30 g / cm 3 Above 0.60g / cm 3Regarding the range of apparent density, the lower limit is preferably 0.30 g / cm 3 More preferably, 0.33 g / cm 3 More preferably, 0.35 g / cm 3 The above results in a long fiber nonwoven fabric having excellent mechanical strength. In addition, regarding the range of apparent density, the upper limit is preferably 0.60 g / cm 3 Below, more preferably 0.55g / cm 3 Below, more preferably 0.50 g / cm 3 The long-fiber nonwoven fabric thus obtained has appropriate softness. Furthermore, the nonwoven fabric has advantages in workability during sewing as an airbag packaging material and during storage in an airbag component.
[0069] It should be noted that in the present invention, the apparent density (g / cm 3 ) is the value obtained by the following formula using the values of the weight per unit area and thickness of the long-fiber nonwoven fabric measured by the aforementioned method.
[0070] Apparent density (g / cm 3 ) = weight per unit area (g / m 2 ) / Thickness(mm) / 1,000.
[0071] In the present invention, it is preferred that the tear strength of the long fiber nonwoven fabric in the longitudinal direction and the cross direction are both 30 N or more and 120 N or less. It should be noted that when the longitudinal direction can be determined based on the appearance of the long fiber nonwoven fabric, that is, when the winding direction of the nonwoven fabric roll can be uniquely determined, this method is used as the longitudinal direction. On the other hand, when the long fiber nonwoven fabric is not in a roll state, such as when it is cut, the longitudinal direction and the cross direction cannot be determined based on the appearance, the following steps are used to determine.
[0072] (a) In the surface of the long-fiber nonwoven fabric, determine any one direction and collect a test piece having a length of 30 cm and a width of 5.0 cm along the direction.
[0073] (b) Similarly, a test piece having a length of 30 cm and a width of 5.0 cm is sampled in directions rotated 30 degrees, 60 degrees, and 90 degrees from the sampling direction.
[0074] (c) For the test pieces in each direction, the tensile strength of each test piece is measured based on the method for measuring the tensile strength of the long fiber nonwoven fabric shown in the following (c-1) to (c-3). It should be noted that the tensile strength (N / 5cm) in the longitudinal direction and the cross direction of the long fiber nonwoven fabric of the present invention is the value measured as follows based on 6.3 "Tensile strength and elongation" of JIS L 1913:2010 "General long fiber nonwoven fabric test methods".
[0075] (c-1) Five samples of 30 cm x 5.0 cm in width are collected from the nonwoven fabric at equal intervals in the longitudinal direction and the cross direction (for example, when the tensile strength in the cross direction is to be determined, the samples are collected at equal intervals in the longitudinal direction).
[0076] (c-2) A load is applied under the conditions of a clamping interval of 20 cm and a tensile speed of 100±10 mm / min until the sample is cut.
[0077] (c-3) The strength of the sample at the maximum load is taken as the tensile strength (N / 5 cm), the average value of 5 points is calculated, and the value obtained by rounding off the first decimal place is taken as the tensile strength in the longitudinal direction and the cross direction of the long fiber nonwoven fabric.
[0078] (d) The direction with the highest value obtained by the measurement is taken as the length direction of the long fiber nonwoven fabric, and the direction orthogonal thereto is taken as the cross direction. When the highest direction is in two or more directions, the direction in which the tensile strength in the direction orthogonal to these directions becomes lower is taken as the length direction of the long fiber nonwoven fabric. When the highest direction is in two or more directions, when the tensile strength in the direction orthogonal to these directions is also equal, for example, when the tensile strength in four directions is all equal, any one of the four directions is taken as the length direction, and the direction orthogonal thereto is taken as the cross direction.
[0079] The lower limits of the tear strength in the longitudinal direction and the cross direction are preferably 30 N or more, and more preferably 40 N or more, thereby suppressing the filmization and property degradation of the nonwoven surface caused by excessive thermal bonding, and forming a long-fiber nonwoven fabric with appropriate softness. In addition, the upper limits of the tear strength in the longitudinal direction and the cross direction are preferably 120 N or less, and more preferably 110 N or less, thereby allowing the fibers constituting the long-fiber nonwoven fabric to be thermally bonded appropriately to form a long-fiber nonwoven fabric with appropriate mechanical properties.
[0080] It should be noted that in the present invention, the tear strength in the longitudinal direction and the cross direction of the long fiber nonwoven fabric is measured using a constant rate elongation type tensile testing machine ("RTG-1250" manufactured by BALDWIN CORPORATION or a constant rate elongation type tensile testing machine having equivalent performance) in accordance with JIS L 1913:2010 "General nonwoven fabric test methods" 6.4 "Tear strength" a) Trapezoid method, and the values are obtained as follows.
[0081] (i) Five samples of 25 cm x 5.0 cm in width are collected from the long-fiber nonwoven fabric at equal intervals in the longitudinal direction and the cross direction (for example, when the tear strength in the cross direction is determined, the samples are collected at equal intervals in the longitudinal direction).
[0082] (ii) An isosceles trapezoidal mark is made on the test piece, and a 1.0 cm notch is made at a right angle to the short side in the center of the short side of the mark.
[0083] (iii) The test piece was mounted on a jig along the mark using a constant rate extension type tensile testing machine with a clamping interval of 10 cm so that the short sides of the trapezoid were stretched and the long sides were relaxed.
[0084] (iv) Under the condition of a tensile speed of 100±10 mm / min, the maximum load (N) at the time of tearing is taken as the tear strength (N), the average value of 5 points is calculated, and the value obtained by rounding off the first decimal place is taken as the tear strength in the longitudinal direction and the cross direction of the long fiber nonwoven fabric.
[0085] In addition, as a method for making the tear strength of the long-fiber nonwoven fabric in both the longitudinal direction and the cross direction fall within the above-mentioned range, there can be mentioned adjusting the temperature and linear pressure during thermal bonding as described later.
[0086] The tensile elongation of the long fiber nonwoven fabric of the present invention in both the longitudinal direction and the cross direction is preferably set to 10% or more and 40% or less. By treating in this way, a long fiber nonwoven fabric having both mechanical strength and appropriate softness can be obtained.
[0087] The tensile elongation (%) in the longitudinal direction and the cross direction of the long-fiber nonwoven fabric was measured as follows in accordance with 6.3 "Tensile strength and elongation" of JIS L 1913:2010 "General long-fiber nonwoven fabric test methods".
[0088] (i) Five samples of 30 cm x 5.0 cm in width are collected from the long-fiber nonwoven fabric at equal intervals in both the longitudinal direction and the cross direction (for example, when determining the tensile elongation in the cross direction, at equal intervals in the longitudinal direction).
[0089] (ii) A load is applied under the conditions of a clamping interval of 20 cm and a tensile speed of 100±10 mm / min until the sample is cut.
[0090] (iii) The elongation of the sample at the maximum load is measured up to 1 mm, and the value obtained by calculating the elongation from the elongation is taken as the tensile elongation (%). The average value of 5 points is calculated, and the value obtained by rounding off the first decimal place is taken as the tensile elongation in the longitudinal direction and the cross direction of the long fiber nonwoven fabric.
[0091] In addition, examples of methods for adjusting the tensile elongation of the long-fiber nonwoven fabric to the above range include adjusting the temperature and linear pressure during thermal bonding as described later.
[0092] In the present invention, the surface roughness Rz of the long fiber nonwoven fabric is preferably 50 μm or less on both surfaces. By making the surface roughness Rz as described above, there is no folding of the sheet during the sewing operation, which is advantageous in terms of operability. In addition, the long fiber nonwoven fabric is not continuously torn from a certain point during the airbag storage operation and maintains mechanical strength.
[0093] In addition, the surface roughness Rz (μm) of the long-fiber nonwoven fabric was calculated by the following procedure.
[0094] (1) Test pieces of 10 cm x 10 cm were collected from 20 random locations on the long-fiber nonwoven fabric.
[0095] (2) For each test piece, a surface roughness meter ("Surftest SJ-210" manufactured by Mitutoyo Corporation or a surface roughness meter having equivalent performance) was used in accordance with JIS B 0610:2001 "Geometric Properties Specification for Products (GPS) - Surface Shape: Profile Curve Method - Definition and Expression of Rolling Circular Waviness", under the conditions of λc = 2.5 mm, λs = 8 μm, and a measuring speed of 0.5 mm / s. The maximum height Rz was measured over a range of 21 mm in the direction intersecting the long-fiber nonwoven fabric, and the maximum height Rz was implemented on each surface in units of 0.1 μm.
[0096] (3) Repeat (2) for each test piece, calculate the arithmetic mean (μm) of the maximum height Rz, round off to the first decimal place, and use it as the surface roughness Rz (μm).
[0097] [Method for producing long-fiber nonwoven fabric]
[0098] Next, the method for producing the long-fiber nonwoven fabric of the present invention will be described. The long-fiber nonwoven fabric of the present invention is preferably produced by sequentially carrying out the following steps (a) to (c).
[0099] (a) A step of melt-extruding a thermoplastic resin from a spinneret and pulling and stretching the spun thermoplastic resin using an ejector to form fibers.
[0100] (b) A step of controlling the arrangement of the fibers using a fiber spreading sheet and depositing the fibers on a moving net conveyor to form a fiber web.
[0101] (c) The obtained fiber web is preheated and then subjected to a thermal bonding step.
[0102] Hereinafter, each of the above steps will be described in more detail.
[0103] (a) Fiber Forming Process
[0104] First, in this process, the thermoplastic resin is melt-extruded from a spinneret. In particular, when the fiber constituting the long fiber nonwoven fabric is a composite fiber in which a low-melting polymer having a melting point lower than the melting point of the high-melting polymer is arranged around the high-melting polymer, the high-melting polymer and the low-melting polymer are melted at a temperature above their melting points (melting point + 70°C) and below, respectively, and preferably melt-extruded from a spinneret having a spinneret temperature above the melting point and below (melting point + 70°C) so that a low-melting polymer having a melting point lower than the melting point of the high-melting polymer by 10°C or more and 140°C or less is arranged around the high-melting polymer. In addition, the shape of the ejection hole of the spinneret for extruding the molten thermoplastic resin is consistent with the cross-sectional shape of the aforementioned fiber, and a circular, elliptical, polygonal, multi-lobal, or a combination thereof can be cited. Among them, from the viewpoint of being able to efficiently obtain bonding points between the fibers and firmly bonding the fibers to each other by thermocompression bonding, it is more preferable to use an ejection hole with a circular cross-sectional shape.
[0105] Then, melt extrusion is performed as described above, and the spun thermoplastic resin is pulled and stretched by an ejector to form fibers. At this time, the spinning speed is preferably 3,000 m / min to 6,000 m / min.
[0106] (b) Process of forming a fiber web
[0107] In this step, the arrangement of the fibers formed by the above-mentioned steps is controlled by using a fiber spreader. Specifically, it is preferred that the fibers sucked by the ejector are ejected from a fiber spreader having a slit shape provided at the bottom of the ejector. Furthermore, it is preferred that the fibers are deposited on a moving net conveyor to form a fiber web.
[0108] (c) Step of thermally bonding the fiber web
[0109] In the method for producing a long-fiber nonwoven fabric of the present invention, the fiber web obtained in the above steps is preheated and then thermally bonded.
[0110] First, for preheating, preferably, a method of fusing the collected fiber web with a pair of upper and lower flat rolls or a method of installing a flat roll on a net conveyor and fusing the fiber web between the net conveyor and the flat roll is used.
[0111] The "flat roll" used in these preheating methods refers to a metal roll or elastic roll with no unevenness on the roll surface. Furthermore, the so-called upper and lower flat rolls refer to a pair of metal rolls and metal rolls, or a pair of metal rolls and elastic rolls. Here, the so-called elastic roll refers to a roll made of a material that is more elastic than a metal roll. Examples of the elastic roll include so-called paper rolls made of paper, cotton, aramid paper, etc., and resin rolls made of urethane resins, epoxy resins, silicone resins, polyester resins, hard rubber, etc., or mixtures thereof.
[0112] The temperature of the upper and lower flat rollers (or the surface of the preheating device that contacts the nonwoven web when not using them) during preheating is preferably set to a temperature that is 65°C or higher and 120°C or lower than the melting point of the thermoplastic resin (in the case of composite fibers in which a low melting point polymer having a melting point lower than that of a high melting point polymer is arranged around a high melting point polymer, the melting point of the low melting point polymer). By setting the temperature to such a level, the fibers will not be excessively fused to each other, and the conveyance performance during the production of the long-fiber nonwoven fabric can be improved.
[0113] In addition, the linear pressure during preheating is preferably 40 N / cm or more and 1,000 N / cm or less. By setting the linear pressure for preheating to 40 N / cm or more, the mechanical strength required for conveying the fiber web to the next step can be imparted. On the other hand, by setting the linear pressure for preheating to 1,000 N / cm or less, excessive fusion of fibers can be prevented.
[0114] Next, the preheated fiber web is subjected to thermal bonding. This thermal bonding is also preferably performed using a pair of upper and lower flat rollers. Among them, from the perspective of being able to produce a long-fiber nonwoven fabric with excellent smoothness and small thickness deviation in the width direction, it is more preferable to use a pair of metal rollers. When this combination is used, the thickness and mechanical properties of the long-fiber nonwoven fabric can be made more uniform.
[0115] The temperature of the upper and lower flat rollers (when not used, the surface of the preheating device that contacts the nonwoven web) during thermal bonding is preferably set to a temperature that is 5°C or more and 60°C or less lower than the melting point of the thermoplastic resin (in the case of a composite fiber in which a low-melting-point polymer having a melting point lower than that of the high-melting-point polymer is arranged around a high-melting-point polymer, the melting point of the low-melting-point polymer). By setting the temperature in this way, it is possible to suppress excessive fusion of the fibers and to suppress the long-fiber nonwoven from partially forming a sheet-like film. In addition, it is possible to suppress the situation in which the low-melting-point polymer component is fused to the roller used during thermal bonding, thereby reducing productivity.
[0116] The linear pressure of thermal bonding is preferably 90 N / cm or more and 1,000 N / cm or less. By setting the linear pressure for thermal bonding to 90 N / cm or more, a long-fiber nonwoven fabric having excellent mechanical strength can be produced. By setting the linear pressure for thermal bonding to 1,000 N / cm or less, excessive fusion of fibers can be prevented.
[0117] In the method for producing a long fiber nonwoven fabric of the present invention, the above-mentioned preheating and thermal bonding can be performed continuously on one production line, or the preheating can be performed by winding once and unwinding again to perform thermal bonding. Among them, from the perspective of excellent productivity, it is preferred to perform preheating and thermal bonding continuously on one production line.
[0118] [Airbag packaging materials]
[0119] The airbag packaging material of the present invention is an airbag packaging material comprising the long fiber nonwoven fabric. Moreover, it is preferred that a flame retardant layer is provided on at least one side of the long fiber nonwoven fabric. Specifically, it is preferred that a flame retardant layer is provided on the inner and / or outer surfaces of the airbag packaging material that accommodates the airbag. By providing the flame retardant layer, an airbag packaging material having high flame retardancy, which is an important indicator of the airbag packaging material, can be produced.
[0120] When a flame retardant layer is provided on the long-fiber nonwoven fabric of the present invention, the mass of the flame retardant layer per unit area of the long-fiber nonwoven fabric is preferably 0.1 g / m 2 Above 5.0g / m 2 By setting the mass per unit area of the flame retardant layer to 0.1 g / m 2 Above, preferably 0.2 g / m 2 In the above, an airbag packaging material having moderate flame retardancy can be prepared. In addition, by setting the mass per unit area of the flame retardant layer to 5.0 g / m 2 Below, preferably set to 4.0g / m 2 Hereby, it is possible to suppress the reduction in mechanical properties due to the sealing effect on the surface of the nonwoven fabric.
[0121] When the flame retardant layer is provided, the mass concentration of the flame retardant in the flame retardant solution used is preferably 5% to 20%. By setting the mass concentration of the flame retardant to such a range, an airbag packaging material having moderate flame retardancy can be produced. The solvent for diluting the flame retardant is not particularly specified, and by using water, a more environmentally friendly manufacturing method can be achieved. In addition, the flame retardant is preferably a halogen-based, phosphorus-based, composite-based organic flame retardant, or a metal hydroxide, antimony-based inorganic flame retardant.
[0122] As a method for providing the flame retardant layer on the long-fiber nonwoven fabric of the present invention, a method of applying the flame retardant solution by a gravure coating method, a gravure offset coating method, a flexographic coating method, a roll coating method, a comma coating method, a knife coating method or the like is preferred.
[0123] In addition, other additives may be added to the flame retardant solution within the scope of not impairing the purpose of the present invention, such as water repellent, antistatic agent, penetrant, etc. These processing agents are mixed in the above-mentioned solvent and applied to the long fiber nonwoven fabric.
[0124] Example
[0125] Next, the long fiber nonwoven fabric of the present invention is specifically described based on examples. However, the present invention is not limited to these examples. It should be noted that in the measurement of various physical properties, unless otherwise specified, the measurement was performed based on the above-mentioned method.
[0126] [Measurement method]
[0127] (1) Melting point of polyester (℃)
[0128] The measurement was performed using a differential scanning calorimeter "DSC-2" (manufactured by PerkinElmer) at a temperature increase rate of 20°C / min, and the temperature at which the extreme value of the obtained melting endothermic curve was obtained was defined as the melting point.
[0129] (2) Intrinsic viscosity (IV) of polyester
[0130] Regarding the intrinsic viscosity (IV) of the polyester, 8 g of a sample was dissolved in 100 mL of o-chlorophenol, and the relative viscosity η was determined using an Ostwald viscometer at 25° C. using the following formula: r .
[0131] η r =η / η0=(t×d) / (t0×d0)
[0132] (Here, η represents the viscosity of the polymer solution, η0 represents the viscosity of o-chlorophenol, t represents the falling time of the solution (seconds), and d represents the density of the solution (g / cm3 ), t0 represents the falling time of o-chlorophenol (seconds), d0 represents the density of o-chlorophenol (g / cm 3 ). )
[0133] Next, the relative viscosity η r The intrinsic viscosity (IV) was calculated by the following formula.
[0134] Intrinsic viscosity (IV) = 0.0242η r +0.2634.
[0135] (3) Average single fiber diameter (μm)
[0136] The average single fiber diameter of the fibers used in the present invention is calculated by the above-mentioned method using SEM ("VHX-D500" manufactured by KEYENCE CORPORATION).
[0137] (4) Weight per unit area of long fiber nonwoven fabric (g / m 2 )
[0138] The weight per unit area of the long-fiber nonwoven fabric was calculated by the above-mentioned method.
[0139] (5) Thickness of long fiber nonwoven fabric (mm)
[0140] The thickness of the long-fiber nonwoven fabric was evaluated by the above-described method using a thickness meter "TECLOCK" (registered trademark) SM-114 (manufactured by TECLOCK Co., Ltd.).
[0141] (6) Density of long fiber nonwoven fabric (g / cm 3 )
[0142] The density of the long-fiber nonwoven fabric was calculated by the above-mentioned method.
[0143] (7) Cross-sectional void ratio of long fiber nonwoven fabric (%)
[0144] The cross-sectional void ratio of the long-fiber nonwoven fabric was calculated by the above-mentioned method.
[0145] (8) Tearing strength of long fiber nonwoven fabric (N)
[0146] The tear strength of the long-fiber nonwoven fabric was calculated by the above-mentioned method.
[0147] (9) Tensile elongation of long fiber nonwoven fabric (%)
[0148] The tensile elongation of the long-fiber nonwoven fabric was calculated by the above-mentioned method.
[0149] (10) Sewing operability of long-fiber nonwoven fabrics
[0150] The long-fiber nonwoven fabric was cut into a rectangle of 30 cm in width and 50 cm in length, and the short sides were overlapped to form a size of 30 cm in width and 25 cm in length. A wave stitch process was performed manually at a pitch of 4 mm using No. 60 nylon sewing thread (manufactured by FUJIX Ltd.) in the portion 10 mm inward from the end of the overlapping portion. The operation was confirmed by 20 healthy men and women, and the sewing operability when made into a bag shape was evaluated according to the following 4 levels of A to D, and the highest evaluation was taken as the sewing operability of the long-fiber nonwoven fabric.
[0151] A: There was no damage to the long-fiber nonwoven fabric, no thread clogging due to the hardness of the long-fiber nonwoven fabric, and no difficulty in threading the thread.
[0152] B: There is no damage to the long-fiber nonwoven fabric, but there is thread clogging or difficulty in thread penetration.
[0153] C: There is damage to the long-fiber nonwoven fabric, but there is no thread clogging or difficulty in thread penetration.
[0154] D: Damage of the long-fiber nonwoven fabric was observed, and the threads were clogged or had difficulty passing through.
[0155] [Resin used]
[0156] Next, the details of the resins used in Examples and Comparative Examples are described.
[0157] · High melting point polymer: polyethylene terephthalate (PET) dried to a water content of 50 mass ppm or less, having an intrinsic viscosity (IV) of 0.65 and a melting point of 260°C.
[0158] Low melting point polymer: copolymerized polyethylene terephthalate (co-PET) having an intrinsic viscosity (IV) of 0.64 and an isophthalic acid copolymerization ratio of 11 mol % and a melting point of 230° C. dried to a water content of 50 ppm by mass or less.
[0159] [Example 1]
[0160] (Fiber Forming Process)
[0161] The high melting point polymer and the low melting point polymer were melted at 295° C. and 280° C., respectively. Then, the high melting point polymer was used as the core component and the low melting point polymer was used as the sheath component. The fibers were spun from the ejection hole of a circular spinneret at a mass ratio of core:sheath=80:20 at a spinneret temperature of 295° C., and then pulled by an ejector at a spinning speed of 4,900 m / min to spin a composite fiber having a circular cross-sectional shape.
[0162] (Process of forming a fiber web)
[0163] The arrangement of the composite fibers was controlled by a spread sheet, and the composite fibers were deposited on a moving net conveyor to collect and form a fiber web made of fibers having an average single fiber diameter of 15.5 μm.
[0164] (Process of thermally bonding the fiber web)
[0165] The captured fiber web was preheated at a temperature of 135°C and a linear pressure of 45 N / cm by a metal flat roll MFC1 installed on a net conveyor. Then, the fiber web was thermally bonded by a calender roll MFC2 consisting of a pair of metal flat rolls at a temperature of 150°C and a linear pressure of 450 N / cm to obtain a long-fiber nonwoven fabric. The unit weight of the long-fiber nonwoven fabric was 55 g / m 2 , thickness is 0.13mm, density is 0.42g / cm 3 The tear strength in the longitudinal direction was 59N, the tear strength in the cross direction was 78N, the tensile elongation in the longitudinal direction was 27%, the tensile elongation in the cross direction was 20%, and the cross-sectional void ratio was 45%. In addition, the sewing workability was A. The results are shown in Table 1.
[0166] [Example 2]
[0167] In the process of forming the fiber web, the speed of the moving net conveyor is changed to increase the unit area weight of the long fiber nonwoven fabric from 55g / m 2 Change to 90g / m 2 In the process of thermal bonding the fiber web, the temperature of the metal flat roll MFC1 during preheating was changed from 135°C to 140°C, and the temperature of the calender roll MFC2 during thermal bonding was changed from 150°C to 170°C. The same operation as in Example 1 was performed to obtain a long fiber nonwoven fabric. The long fiber nonwoven fabric had a thickness of 0.15 mm and a density of 0.60 g / cm 3 The tear strength in the longitudinal direction was 72N, the tear strength in the cross direction was 94N, the tensile elongation in the longitudinal direction was 28%, the tensile elongation in the cross direction was 23%, and the cross-sectional void ratio was 60%. In addition, the sewing workability was A. The results are shown in Table 1.
[0168] [Example 3]
[0169] In the fiber forming process, the amount of molten polymer spun from the circular spinneret's ejection hole was changed to change the average single fiber diameter from 15.5 μm to 10.6 μm. In the fiber web forming process, the speed of the moving net conveyor was changed to change the unit area weight of the long fiber nonwoven fabric from 55 g / m 2 Changed to 35g / m 2In the process of thermal bonding the fiber web, the temperature of the metal flat roll MFC1 during preheating was changed from 135°C to 130°C, and the temperature of the calender roll MFC2 during thermal bonding was changed from 150°C to 175°C. The same operation as in Example 1 was performed to obtain a long fiber nonwoven fabric. The long fiber nonwoven fabric had a thickness of 0.06 mm and a density of 0.58 g / cm 3 The tear strength in the longitudinal direction was 32N, the tear strength in the cross direction was 50N, the tensile elongation in the longitudinal direction was 23%, the tensile elongation in the cross direction was 20%, and the cross-sectional void ratio was 75%. In addition, the sewing workability was A. The results are shown in Table 1.
[0170] [Example 4]
[0171] In the process of forming fibers, the amount of molten polymer spun from the orifice of the circular spinneret was changed to change the average single fiber diameter of the fibers from 15.5 μm to 16.7 μm, and in the process of thermally bonding the fiber web, the temperature of the calender roll MFC2 during thermal bonding was changed from 150° C. to 165° C. The same operation as in Example 1 was performed to obtain a long fiber nonwoven fabric. The weight per unit area of the long fiber nonwoven fabric was 55 g / m 2 , thickness is 0.16mm, density is 0.34g / cm 3 The tear strength in the longitudinal direction was 75N, the tear strength in the cross direction was 110N, the tensile elongation in the longitudinal direction was 30%, the tensile elongation in the cross direction was 22%, and the cross-sectional void ratio was 38%. In addition, the sewing workability was A. The results are shown in Table 1.
[0172] [Example 5]
[0173] In the fiber forming process, the mass ratio of the core component formed from the high melting point polymer and the sheath component formed from the low melting point polymer was changed from core:sheath = 80:20 to 70:30, the amount of molten polymer spun from the ejection hole of the circular spinneret was changed, the average single fiber diameter of the fiber was changed from 15.5 μm to 11.2 μm, the spinning speed was changed from 4,900 m / min to 4,100 m / min, and in the fiber web forming process, the speed of the moving net conveyor was changed, and the unit area weight of the long fiber nonwoven fabric was changed from 55 g / m 2 Changed to 40g / m 2 In the process of thermally bonding the fiber web, the temperature of the calender roll MFC2 comprising a pair of metal flat rolls during thermal bonding was changed from 150°C to 160°C. The same operation as in Example 1 was performed to obtain a long fiber nonwoven fabric. The long fiber nonwoven fabric had a thickness of 0.10 mm and a density of 0.40 g / cm 3The tear strength in the longitudinal direction was 48 N, the tear strength in the cross direction was 65 N, the tensile elongation in the longitudinal direction was 25%, the tensile elongation in the cross direction was 18%, and the cross-sectional void ratio was 52%. In addition, the sewing workability was A. The results are shown in Table 1.
[0174] [Example 6]
[0175] In the fiber forming process, the amount of molten polymer spun from the circular spinneret's ejection hole was changed to change the average single fiber diameter from 15.5 μm to 11.9 μm. In the fiber web forming process, the speed of the moving net conveyor was changed to change the unit area weight of the long fiber nonwoven fabric from 55 g / m 2 Changed to 15g / m 2 In the process of thermal bonding the fiber web, the temperature of the metal flat roll MFC1 during preheating was changed from 135°C to 155°C, and the temperature of the calender roll MFC2 during thermal bonding was changed from 150°C to 185°C. The same operation as in Example 1 was performed to obtain a long fiber nonwoven fabric. The long fiber nonwoven fabric had a thickness of 0.04 mm and a density of 0.38 g / cm 3 The tear strength in the longitudinal direction was 12N, the tear strength in the cross direction was 21N, the tensile elongation in the longitudinal direction was 17%, the tensile elongation in the cross direction was 16%, and the cross-sectional void ratio was 30%. In addition, the sewing workability was A. The results are shown in Table 1.
[0176] [Example 7]
[0177] In the fiber forming process, the amount of molten polymer spun from the circular spinneret's ejection hole was changed to change the average single fiber diameter from 15.5 μm to 11.9 μm. In the fiber web forming process, the speed of the moving net conveyor was changed to change the unit area weight of the long fiber nonwoven fabric from 55 g / m 2 Changed to 110g / m 2 In the process of thermal bonding the fiber web, the temperature of the metal flat roll MFC1 during preheating was changed from 135°C to 115°C, and the temperature of the calender roll MFC2 during thermal bonding was changed from 150°C to 185°C. The same operation as in Example 1 was performed to obtain a long fiber nonwoven fabric. The long fiber nonwoven fabric had a thickness of 0.21 mm and a density of 0.52 g / cm 3 The tear strength in the longitudinal direction was 73N, the tear strength in the cross direction was 125N, the tensile elongation in the longitudinal direction was 33%, the tensile elongation in the cross direction was 30%, and the cross-sectional void ratio was 55%. In addition, the sewing workability was A. The results are shown in Table 1.
[0178] [Example 8]
[0179] In the fiber forming process, the amount of molten polymer spun from the circular spinneret's ejection hole was changed to change the average single fiber diameter from 15.5 μm to 10.6 μm. In the fiber web forming process, the speed of the moving net conveyor was changed to change the unit area weight of the long fiber nonwoven fabric from 55 g / m 2 Changed to 37g / m 2 In the process of thermally bonding the fiber web, the temperature of the calender roll MFC2 during thermal bonding was changed from 150°C to 132°C. The same operation as in Example 1 was performed to obtain a long fiber nonwoven fabric. The long fiber nonwoven fabric had a thickness of 0.16 mm and a density of 0.23 g / cm 3 The tear strength in the longitudinal direction was 35N, the tear strength in the cross direction was 48N, the tensile elongation in the longitudinal direction was 5%, the tensile elongation in the cross direction was 10%, and the cross-sectional void ratio was 79%. In addition, the sewing workability was A. The results are shown in Table 1.
[0180] [Comparative Example 1]
[0181] In the fiber forming process, the amount of molten polymer spun from the circular spinneret's ejection hole was changed to change the average single fiber diameter from 15.5 μm to 12.0 μm. In the fiber web forming process, the speed of the moving net conveyor was changed to change the unit area weight of the long fiber nonwoven fabric from 55 g / m 2 Change to 50g / m 2 In the process of thermal bonding the fiber web, the temperature of the metal flat roll MFC1 during preheating was changed from 135°C to 155°C, and the temperature of the calender roll MFC2 during thermal bonding was changed from 150°C to 185°C. The same operation as in Example 1 was performed to obtain a long fiber nonwoven fabric. The long fiber nonwoven fabric had a thickness of 0.08 mm and a density of 0.63 g / cm 3 The tear strength in the longitudinal direction was 30N, the tear strength in the cross direction was 40N, the tensile elongation in the longitudinal direction was 15%, the tensile elongation in the cross direction was 17%, and the cross-sectional void ratio was 95%. In addition, the sewing workability was D. The results are shown in Table 1.
[0182] [Comparative Example 2]
[0183] In the process of forming the fiber web, the speed of the moving net conveyor is changed to increase the unit area weight of the long fiber nonwoven fabric from 55g / m 2 Changed to 110g / m 2In the process of thermal bonding the fiber web, no preheating was performed, and the temperature of the calender roll MFC2 including a pair of metal flat rolls during thermal bonding was changed from 150°C for both the upper and lower flat rolls to 200°C for the upper flat roll and 170°C for the lower flat roll, and the linear pressure was changed from 450 N / cm to 490 N / cm. The same operation was performed as in Example 1 to obtain a long fiber nonwoven fabric. The long fiber nonwoven fabric had a thickness of 0.21 mm and a density of 0.52 g / cm 3 The tear strength in the longitudinal direction was 150 N, the tear strength in the cross direction was 204 N, the tensile elongation in the longitudinal direction was 23%, the tensile elongation in the cross direction was 12%, and the cross-sectional void ratio was 85%. In addition, the sewing workability was B. The results are shown in Table 1.
[0184] [Comparative Example 3]
[0185] In the process of forming fibers, the amount of molten polymer spun from the orifice of the circular spinneret was changed to change the average single fiber diameter from 15.5 μm to 9.7 μm. In the process of forming a fiber web, the speed of the moving net conveyor was changed to change the unit weight of the long fiber nonwoven fabric from 55 g / m 2 Change to 80g / m 2 In the process of thermal bonding the fiber web, no preheating was performed, and the temperature of the calender roll MFC2 including a pair of metal flat rolls during thermal bonding was changed from 150°C for both the upper and lower flat rolls to 190°C for the upper flat roll and 180°C for the lower flat roll, and the linear pressure was changed from 450N / cm to 580N / cm. The same operation was performed as in Example 1 to obtain a long fiber nonwoven fabric. The long fiber nonwoven fabric had a thickness of 0.10 mm and a density of 0.80 g / cm 3 The tear strength in the longitudinal direction was 4N, the tear strength in the cross direction was 25N, the tensile elongation in the longitudinal direction was 35%, the tensile elongation in the cross direction was 25%, and the cross-sectional void ratio was 14%. In addition, the sewing workability was D. The results are shown in Table 1.
[0186] [Comparative Example 4]
[0187] In the fiber forming process, the amount of molten polymer spun from the circular spinneret’s ejection hole was changed, the average single fiber diameter of the fiber was changed from 15.5 μm to 16.1 μm, the spinning speed was changed from 4,900 m / min to 4,300 m / min, the speed of the moving net conveyor was changed, and the weight per unit area of the long fiber nonwoven fabric was increased from 55 g / m 2 Change to 200g / m 2In the process of thermally bonding the fiber web, after passing hot air at a temperature of 250°C through the collected fiber web, thermal bonding was performed using a calender roll MFC2 comprising a pair of flat rolls at a temperature of 180°C and a linear pressure of 490 N / cm. The same operation as in Example 1 was performed to obtain a long fiber nonwoven fabric. The long fiber nonwoven fabric had a thickness of 1.4 mm and a density of 0.14 g / cm 3 The tear strength in the longitudinal direction was 69 N, the tear strength in the cross direction was 88 N, the tensile elongation in the longitudinal direction was 35%, the tensile elongation in the cross direction was 39%, and the cross-sectional void ratio was 81%. In addition, the sewing workability was B. The results are shown in Table 1.
[0188] [Table 1]
[0189]
[0190] The properties of the obtained nonwoven fabric are shown in Table 1. The average single fiber diameter of the long fiber nonwoven fabrics of Examples 1 to 4 is not less than 10.0 μm and not more than 20.0 μm, and the cross-sectional porosity is not less than 30% and not more than 80%. Therefore, the tear strength in the longitudinal direction and the cross direction is not less than 30 N and not more than 120 N, and the tensile elongation in the longitudinal direction and the cross direction is not less than 10% and not more than 40%. There is no problem with sewing operability, showing the characteristics of long fiber nonwoven fabrics that have both moderate density and sufficient mechanical strength. In addition, although the long fiber nonwoven fabric of Example 6 has low unit weight and tear strength, the average single fiber diameter is 10.0 μm or more and 20.0 μm or less, and the cross-sectional void ratio is 30% or more and 80% or less, and there is no problem in sewing workability. Although the long fiber nonwoven fabric of Example 7 has high unit weight and tear strength, the average single fiber diameter is 10.0 μm or more and 20.0 μm or less, and the cross-sectional void ratio is 30% or more and 80% or less, there is no problem in sewing workability. Although the long fiber nonwoven fabric of Example 8 has low tensile elongation, the average single fiber diameter is 10.0 μm or more and 20.0 μm or less, and the cross-sectional void ratio is 30% or more and 80% or less, there is no problem in sewing workability. Examples 6 to 8 all show the characteristics of long fiber nonwoven fabrics with appropriate density. On the other hand, the sheets of Comparative Examples 1 and 3 are hard and poor in mechanical strength. Comparative Examples 2 and 4 are thick and fuzzy nonwoven fabrics, which are inferior.
[0191] Industrial Applicability
[0192] The long-fiber nonwoven fabric of the present invention can be used as a raw material for airbag packaging materials because it has excellent flexibility to follow the device form of the airbag storage member and excellent mechanical strength to avoid damage or tearing when in contact with the airbag storage member.
Claims
1. A long-fiber nonwoven fabric comprising fibers mainly composed of a thermoplastic resin, wherein the average single fiber diameter of the fibers is 10.0 μm to 20.0 μm, and the cross-sectional void ratio of the long-fiber nonwoven fabric is 30% to 80%.
2. The long fiber nonwoven fabric according to claim 1, wherein: The fiber is a composite fiber in which a low melting point polymer having a melting point lower than that of the high melting point polymer is arranged around a high melting point polymer.
3. The long fiber nonwoven fabric according to claim 1 or 2, wherein: The unit weight of long fiber nonwoven fabric is 20g / m 2 Above 100g / m 2 the following.
4. The long fiber nonwoven fabric according to claim 1 or 2, wherein: The long-fiber nonwoven fabric has a tear strength of 30 N to 120 N in both the longitudinal and cross directions, and a tensile elongation of 10% to 40% in both the longitudinal and cross directions.
5. An air bag packaging material comprising the long-fiber nonwoven fabric according to claim 1 or 2.
6. The method for producing a long-fiber nonwoven fabric according to claim 1, wherein the following steps (a) to (c) are performed in sequence: (a) a step of melt-extruding a thermoplastic resin from a spinneret and pulling and stretching the spun thermoplastic resin using an ejector to form fibers; (b) a process of controlling the arrangement of the fibers by using a fiberboard and depositing them on a moving net conveyor to form a fiber web; (c) The obtained fiber web is preheated and then subjected to a thermal bonding step.
Citation Information
Patent Citations
Curtain-shaped airbag storing wrapping material and storing structure
JP2003306118A
Envelope for side airbags
EP1213194A2
Protective sleeve for airbag
EP1285820A1
Filament nonwoven fabric for forming, its production and container-shaped article using the nonwoven fabric
JP2000096417A
Wrapping material for airbag
JP2004204408A
Cited By
C-shaped water-absorbing core body based on long fiber diversion and preparation method of C-shaped water-absorbing core body
CN120938731A
Rapid absorption flow guide cloth and preparation method thereof
CN121081206A
SAP-free water absorption core for sanitary napkin and preparation method of SAP-free water absorption core
CN121129563A